A photographic key to the adult female biting midges (Diptera: Ceratopogonidae: Culicoides) of Florida, USA - Blosser, Erik M.; Mcgregor, Bethany L.; Burkett-Cadena, Nathan D. (Zootaxa, 2024)
The biting midges (Diptera: Ceratopogonidae: Culicoides) are a diverse group of blood-feeding flies that includes numerous pest and vector species. Major gaps exist in our knowledge of the biology and ecology of the majority of Culicoides spp., due in part to a lack of keys for identifying the biting midges of a given region. In Florida, USA, The Sand Flies of Florida (Blanton and Wirth, 1979) has been a foundational resource for biting midge identification since its publication. The identification keys to the 47 biting midge species (and one subspecies) in The Sand Flies of Florida are not illustrated, however, and frequently rely upon microscopic features (spermathecae, antennal sensory pattern, number of teeth on mandible) as discriminating characters. Here we provide an updated photographic key to 49 nominal species of Culicoides from Florida, USA. The revised key orders characters so that species of nuisance, medical or veterinary importance can be reliably identified without slide mounting, an aspect that should facilitate ecological field work. Synoptic tables summarize the taxonomic affinity, distribution, abundance, seasonality, and medical / veterinary importance of the Culicoides spp. from Florida, compiled from published sources.